A atualidade da proposta educação para o pensar de Mathew Lipman diante das políticas para o ensino de filosofia - Madaloz, Marcos Antônio Martinelli (2018)
This investigation has as its main aim to appreciate the approach Education for thinking, from Mathew Lipman (1990;1994;1995;1997) who, by means of a critical and creative thinking searches to enhance cognitive abilities face to the complex, plural and technological challenges of the contemporary society. It intends to answer, resorting to sources of documental and bibliographical nature, the following question: Is the proposal Education for thinking, still promising to face the educational challenges nowadays?Guided by this question, the study is divided in three parts: in the first one it contextualizes the intellectual heritage of Lipman and its influence in the proposal Education for thinking, the pedagogical experience of Dewey, the experience as an education value and the intellectual trajectory of Lipman; in the second, it presents the pillars of the program Education for thinking, with the higher level of thinking, the cognitive abilities, the investigative dialogue, the community of investigation the Education for thinking and the school subjects; and in the third it analyses the contemporaneity of this pillars face to the educational challenges. Among the results of the study one highlights the contemporaneity of the Lipmanian purpose face to the BNCC (2018) in the aspects of the general and specific competences in the areas of applied Human and Social Sciences as well as to the formation of education professionals for the practice of this proposa.